Pengaruh Kepatuhan Berhijab Terhadap Perilaku Keagamaan Siswi di SMA Al Falah Cibinong Bogor - Hilda Nurahmah; Alek Maulana; Nana Mulyana (Yayasan Al-Afif, 2026)
This research aims to analyze the influence of hijab adherence on the religious behavior of female students at SMA Al Falah Cibinong Bogor. The phenomenon underlying this research is the importance of examining whether the obligation to wear the hijab at school has been internalized as a spiritual value or is merely a formality of adhering to school regulations. The method used in this research is correlational quantitative with 94 female students as respondents, utilizing a questionnaire as the main instrument and statistical analysis techniques to test the validity and reliability of the data. Data on hijab adherence is measured thru indicators of understanding, consistency, compliance with rules, and internal motivation in its practice. Meanwhile, religious behavior is measured thru indicators of worship practices, personal morals, social morals, obedience, norms, religious commitment, enthusiasm for religious knowledge, respect for religious symbols, and interaction with the Qur'an. The results of this study indicate that the level of hijab adherence and religious behavior among the female students falls into a high category. Data analysis proves the existence of a positive and significant influence between hijab adherence and religious behavior. This indicates that the higher the level of adherence among female students in wearing the hijab, the better their religious behavior will be, which will be reflected in their daily lives. This result serves as a foundation for the school to continue strengthening spiritual guidance so that wearing the hijab becomes a personal awareness for the students, not just a rule in the code of conduct.